The Influence of External Stimuli on Impulsive Buying Behaviour - DR. SYED HAIDER KHALIL; ALI RAZA (Journal of Business & Tourism, 2021)
The aim of current study is to critically examine impulse buying behaviour of customers through the lens of external stimuli. The current study provides a plethora of evidences to extend our knowledge about the behavioural aspects of consumers and key factors of buying decision. The current study looked into External Stimuli through sub factors such as Store Environment, Income Level, Window Display, Credit Card and Visual merchandising to examine their significance on impulse buying. For finding the correlation and interconnectedness of impulsive buying with the above-mentioned factors, we collected primary data through questionnaire survey, which was then analysed using quantitative analysis method. The findings of our study suggest that Store Environment and Income level are highly influential on impulsive buying behaviour whereas the use of credit card has the least impact on impulsive buying behaviour.